Answer:
f(g) = -3( x^2 -x-6) -6 = -3x^2+3x+12
Answer:
c = -6
Step-by-step explanation:
Let us solve your equation step-by-step, which is this: c
/−3 + 5 = 7
The first step is to simplify both sides of the equation: −1
/3
c + 5 = 7
Then, subtract 5 from both sides: -1/3c + 5 - 5 = 7 - 5 ---> -1/3c = 2
Multiply both sides by -3/1 making it equal to: c = -6.
Answer:
=20000000 (let me know if it's incorrect)
Step-by-step explanation:
A solution of a function is where the function hits the x-axis, so if y is any number that is not equal to 0, there is no possible way that point can be a solution.
Hope this helps!